Prenylated xanthones as potential antiplasmodial substances - Wilawan Mahabusarakam (2018)
Mangostin, the major xanthone of Garcinia mangostana, and a series of synthetic derivatives were investigated for their in vitro antiplasmodial activity against Plasmodium falciparum. Mangostin itself showed moderate activity, but prenylated xanthones containing alkylamino functional groups exhibited quite potent antiplasmodial activity. Some structure-activity relationships are proposed. © Georg Thieme Verlag KG Stuttgart.